EVALUATION OF ORAL HEALTH STATUS BASED ON ORAL HYGIENE PRACTICES IN CHILDREN-A RETROSPECTIVE STUDY - binti Shahroom, Nor Syakirah; Nasim, Jessy,Iffat (International Journal of Psychosocial Rehabilitation, 2025)
Good oral hygiene practices are recommended by the dentist to prevent oral diseases such as dental caries and periodontal diseases. Brushing twice daily with fluoridated toothpaste is the primary preventive method to maintain good oral hygiene and is found to be the most effective hygiene practice. A retrospective study was conducted to assess the association between oral hygiene and the frequency of tooth brushing among children visiting a dental hospital. 531 participants between 7 and 12 years of age were selected randomly for this study. Data variables including socio-demographic data such as age and gender and oral hygiene practices including frequency of brushing and type of toothpaste used were recorded. Oral hygiene index-simplified (OHI-S) was also recorded. All the data were analyzed using the chi-square test. The study revealed that those who brushed twice daily had a lower OHI-S score, which was statistically significant with p<0.05. A statistically significant difference was found between the type of toothpaste and OHI-S score with p<0.05. The children who brushed using fluoridated toothpaste had lower OHI-S scores. There was also a statistically significant difference between gender and frequency of brushing with p<0.05, in which females had good oral hygiene practice compared to males. Thus, it can be concluded that there was a significant association between oral hygiene and the frequency of tooth brushing. Brushing twice daily with fluoridated toothpaste is proven to improve oral health.